Factors influencing buying behaviours of counterfeit products among youths / Jerry Mandau - Mandau, Jerry (Faculty of Business and Management, UITM Sarawak, 2015)
The purpose of this study is to investigate the factors influencing buying behaviours of counterfeit products among youths. This study is to investigate what and why youths like to purchase counterfeit products and the factors that influence them to buy the counterfeit products. The data is collected through self-administered questionnaire which have 250 respondents of selected youths that experience in buying the counterfeit products. The finding revealed that there is factor relationship that influenced the youths to purchase the counterfeit products between purchase intention and word-of-mouth but an opposite for volume of purchase. Based on the results, it can be said the social status is the factor that influence the youths to purchase the counterfeit products and has strong relationship between purchase intention and word-of-mouth.